Ion conduction film with ultra-high porosity structure, preparation method of ion conduction film and battery

Through the combination of the hierarchical progressive pore channel structure and polymer material, the problem of taking into account both porosity and pore size in the flow battery is solved, and the efficiency and performance of the battery are improved.

CN119286050AInactive Publication Date: 2025-01-10ENERFLOW TECH CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411639886.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-01-10
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The prior art is difficult to achieve both high porosity and small pore size in the flow battery, which makes it difficult to improve the balance relationship between current efficiency and voltage efficiency, limiting the application performance of porous membranes in flow battery.

Method used

Through the construction of a hierarchical pore channel structure, combining hydrophobic polymer materials and hydrophilic polymer materials, wet film formation, pore formation and phase separation steps are adopted to achieve the preparation of ultra-high porosity porous membranes to ensure the pore size is nanometers Within the range of stages, a cross-linked network structure is formed to improve mechanical strength and dimensional stability.

Benefits of technology

The balance between porosity and pore size is achieved, the current efficiency, voltage efficiency and energy efficiency of the flow battery are improved, and the overall performance of the battery is significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention provides an ion conducting membrane with an ultra-high porosity structure, a preparation method of the ion conducting membrane and a battery, the ion conducting membrane has a porous structure, the ion conducting membrane comprises a hydrophobic polymer material and a hydrophilic polymer material, the hydrophilic polymer material has water swelling property, the porosity of the ion-conducting membrane is 80% by volume or more, and the average pore size of the porous structure is 4-30 nm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of polymer materials, and specifically relates to an ion-conducting film with an ultra-high porosity structure and a preparation method thereof, and in particular to an ion-conducting film for battery diaphragms and a preparation method and application thereof, and the ion-conducting film is particularly suitable for use in liquid flow batteries. Background Art

[0002] The ion-conducting membrane is the core component material of the flow battery. First, it transfers hydrogen ions in the electrolyte to complete the internal circuit of the battery; second, it separates the positive and negative electrolytes to prevent cross-mixing; third, it separates the positive and negative current collectors to prevent the battery from short-circuiting.

[0003] The Nafion series of perfluorosulfonic acid membranes produced by DuPont in the United States are the most representative and commercially successful ion-conducting membranes. However, the Nafion membranes have problems such as poor barrier capacity and high cost, which hinder their promotion and application in the further commercialization of flow batteries.

[0004] In recent years, with the increasing depletion of traditional fossil fuels and the environmental pollution caused by them, there is an urgent need to develop environmentally friendly renewable energy. Renewable energy sources such as solar energy, hydropower, and wind energy are intermittent and volatile, and require large-scale energy storage systems to achieve continuous and reliable power output. Liquid flow batteries are one of the most important large-scale energy storage systems, with the advantages of high energy efficiency, large storage capacity, no geographical restrictions, deep discharge depth, long working life, and environmental friendliness. Ion conductive membranes are the most core component materials in liquid flow batteries. Therefore, there are many studies on ion conductive membranes for liquid flow batteries. Among them, the existing technologies mainly adopt Nafion resin and other organic and inorganic materials for blending modification, non-fluorine resin for sulfonation or quaternization modification, hybrid modification of various resins and inorganic fillers, and multi-layer film composite modification. Among them, the classification according to the physical morphology of the membrane is mainly dense membrane and porous membrane, and it can be divided into perfluorinated membrane, partially fluorinated membrane, and non-fluorinated membrane according to whether it contains fluorine (see references 1 to 3).

[0005] In addition, porous membranes have been widely studied as a new mechanism membrane system based on ion sieving. At present, porous membranes are often prepared by thermally induced phase separation (TIPS), non-solvent induced phase separation (NIPS) and other methods to construct the microporous pore structure of the membrane. Reference 4 provides a method for preparing porous membranes by non-solvent induced phase separation, which uses non-solvent induced phase separation after casting the membrane, evaporating the solvent while heating, and then immersing the membrane in deionized water to prepare a porous membrane.

[0006] It can be seen that many studies have been attempted on the preparation of porous membranes suitable for batteries, especially for flow batteries, but there is still room for further exploration in providing better ion conductivity and further improving battery efficiency.

[0007] References:

[0008] Reference 1: CN102881853A

[0009] Reference 2: CN107658478A

[0010] Reference 3: CN109103483A

[0011] Reference 4: CN 112151825 A Summary of the invention

[0012] Problem that the invention aims to solve

[0013] As mentioned above, for the preparation of diaphragms for flow batteries, the pore-forming treatment method is mainly to form a suitable porosity in the diaphragm to obtain good ion conductivity, and it is known that the porosity size and ion conductivity often show a one-sided correspondence.

[0014] However, in a large number of production practices, the inventors of the present invention also found that it is often difficult to prepare a membrane structure with high porosity and extremely small pore size only by the above traditional methods, which forms a paradox that is difficult to balance. This paradox is ultimately reflected in the "trade off" balance between current efficiency and voltage efficiency in liquid flow batteries, making it difficult to increase the final battery energy efficiency to a higher level, thereby greatly reducing the performance advantages of porous membranes in liquid flow batteries.

[0015] In view of such technical problems, the present invention mainly provides a porous membrane with improved properties and a preparation method thereof. According to the scheme of the present invention, the porous membrane can not only have a higher porosity, but also the pore size can be controlled at a smaller size at the nanometer level. As a result, the liquid flow battery using the porous membrane of the present invention can take into account both improved current efficiency and voltage efficiency.

[0016] More specifically, the core of the present invention is to achieve the preparation of ultra-high porosity porous membranes by constructing a graded and progressive pore channel structure in the preparation process of ion-conducting membranes with porous structures, while ensuring the relative pore size distribution range of the nanometer-scale pore size, thereby solving the "paradoxical" contradictory relationship in the prior art that the pore size increases with the increase of porosity, and the pore size decreases with the decrease of porosity. While maintaining the nano-scale microporous structure of the membrane, a porous membrane with ultra-high porosity is prepared, thereby further balancing the contradictory relationship between porosity and pore size. The porous ion-conducting membrane according to the present invention is further applied to liquid flow batteries, showing high battery efficiency, high voltage efficiency and high energy efficiency, and achieving a significant improvement in battery efficiency indicators.

[0017] Solutions for solving problems

[0018] Through practice, the inventors found that the above technical problems can be solved by implementing the following technical solutions:

[0019] [1] An ion conducting membrane, wherein the ion conducting membrane has a porous structure, and the ion conducting membrane includes a hydrophobic polymer material and a hydrophilic polymer material, the hydrophilic polymer material is water-swellable,

[0020] in,

[0021] The porosity of the ion-conducting membrane is greater than 80% by volume, and the average pore size of the porous structure is 4 nm to 30 nm.

[0022] [2] The ion conductive membrane according to [1], wherein the mass ratio of the hydrophobic polymer material to the hydrophilic polymer material in the ion conductive membrane is 1:0.8 to 3.

[0023] [3] The ion-conducting membrane according to [1] or [2], wherein the hydrophilic polymer material has one or more hydrophilic groups in its molecular structure.

[0024] [4] The ion conductive membrane according to any one of [1] to [3], wherein the total content of the hydrophobic polymer material and the hydrophilic polymer material in the ion conductive membrane is 95% by mass or more, based on the total mass of the membrane, and optionally, the ion conductive membrane further comprises one or more processing aids.

[0025] [5] The ion conductive membrane according to any one of [1] to [4], wherein the ion conductive membrane has been cross-linked.

[0026] [6] Furthermore, the present invention also provides a method for preparing an ion conducting membrane according to any one of [1] to [5], wherein the method comprises:

[0027] The steps of wet film formation, primary pore formation, secondary pore formation and phase separation are as follows:

[0028] in:

[0029] In the step of forming the wet film, a composition including a hydrophobic polymer material, a hydrophilic polymer material, an organic diluent and a low molecular weight component is mixed to prepare a wet film;

[0030] In the step of primary pore formation, the organic diluent in the wet film is removed to perform primary pore formation;

[0031] In the step of secondary pore formation, the low molecular weight components in the wet film are removed to perform secondary pore formation;

[0032] In the phase separation step, the hydrophilic polymer material and the hydrophobic polymer material are phase separated by swelling of the hydrophilic polymer material.

[0033] [7] The method according to [6], wherein in the wet film forming step, the composition is substantially uniform in composition; based on the total mass of the composition, the content of the organic diluent is 50%-70% by mass, and the content of the low molecular weight component is 10%-30% by mass.

[0034] [8] The method according to [6] or [7], wherein in the primary pore-forming step, the organic diluent is removed using an extractant, and the extractant is a poor solvent for the hydrophobic polymer material, the hydrophilic polymer material and the low molecular weight component.

[0035] [9] The method according to any one of [6] to [8], wherein in the secondary pore-forming step, the low molecular weight components are removed by an organic solvent, and the organic solvent is a poor solvent for the hydrophobic polymer material and the hydrophilic polymer material.

[0036]

[10] The method according to any one of [6] to [9], wherein in the phase separation step, the hydrophilic polymer material is swollen by an aqueous solvent.

[0037]

[11] The method according to any one of [6] to

[10] , wherein the method further comprises a cross-linking step, wherein a cross-linking structure is formed at least by the hydrophilic groups in the hydrophilic polymer material.

[0038]

[12] The method according to

[11] , wherein the cross-linking step is performed simultaneously with the secondary pore formation.

[0039]

[13] The method according to any one of [6] to

[12] , wherein a dry film (a) is obtained after the first pore-forming step, and the porosity of the dry film (a) is 50% to 65% by volume and the pore size is 10 to 50 nm.

[0040]

[14] A method according to any one of [6] to

[13] , wherein after the secondary pore-forming step, a dry film (b) is obtained, wherein the porosity of the dry film (b) is 65% to 80% by volume and the pore size is 7 to 40 nm.

[0041]

[15] The method according to any one of [6] to

[14] , wherein a dry film (c) is obtained after the phase separation step, and the porosity of the dry film (c) is 80% to 92% by volume and the pore size is 4 to 30 nm.

[0042]

[16] . Furthermore, the present invention also provides a redox battery, wherein the battery includes or uses the ion conductive membrane according to any one of [1] to [5], or includes or uses the ion conductive membrane obtained according to any one of [6] to

[15] .

[0043]

[17] The battery according to

[16] , wherein the battery comprises any one of a flow battery and a fuel cell.

[0044] Effects of the Invention

[0045] By implementing the above technical solution, the present invention can achieve the following technical effects:

[0046] 1) Through the multi-level progressive pore structure construction, the paradoxical relationship between high porosity and small pore size that cannot be achieved at the same time is broken, and a "small and numerous" dense pore structure is obtained. This type of membrane has both ultra-high porosity and nanoscale pore size.

[0047] 2) In the preferred scheme, a cross-linked network structure is allowed to form during the pore-making process, thereby further improving the mechanical strength and dimensional stability of the porous membrane. On the other hand, by controlling the degree of cross-linking, the swelling degree of the porous wet membrane can be adjusted, and the porosity and pore size can be further adjusted.

[0048] 3) The porous membrane with ultra-high porosity and nanopore size obtained by the technical solution of the present invention can be further applied in batteries, especially in flow batteries, to further balance the "trade off" relationship between current efficiency and voltage efficiency, thereby achieving high current efficiency, high voltage efficiency and high energy efficiency. DETAILED DESCRIPTION

[0049] Various exemplary embodiments, features and aspects of the present invention will be described in detail below. The word "exemplary" used here means "used as an example, embodiment or illustrative". Any embodiment described here as "exemplary" is not necessarily interpreted as being superior or better than other embodiments.

[0050] In addition, in order to better illustrate the present invention, numerous specific details are provided in the following specific embodiments. It should be understood by those skilled in the art that the present invention can be implemented without certain specific details. In other examples, methods, means, equipment and steps well known to those skilled in the art are not described in detail in order to highlight the subject matter of the present invention.

[0051] Unless otherwise stated, the units used in this specification are all international standard units, and the numerical values ​​and numerical ranges appearing in the present invention should be understood to include the inevitable systematic errors in industrial production.

[0052] In the present specification, a numerical range expressed using "above" or "below" means a numerical range including the number.

[0053] In this specification, the word "may" means both performing a certain process and not performing a certain process.

[0054] In this specification, the use of "optional" or "optional" indicates that certain substances, components, execution steps, application conditions and other factors are used or not used.

[0055] In this specification, the "normal temperature" or "room temperature" used means an indoor ambient temperature of "23±2°C".

[0056] In this specification, unless otherwise stated, "%" used means weight or mass percentage.

[0057] In this specification, the use of “substantially” means that the standard deviation from a theoretical model or theoretical data is within a range of 2%, preferably within a range of 1%.

[0058] In this specification, when the terms “include” and / or “comprise” are used, they indicate the existence of features, steps, operations, devices, components and / or their combinations.

[0059] In this specification, the references to "some specific / preferred embodiments", "other specific / preferred embodiments", "embodiments", etc., mean that the specific elements (e.g., features, structures, properties and / or characteristics) described in connection with the embodiments are included in at least one embodiment described herein, and may or may not exist in other embodiments. In addition, it should be understood that the elements may be combined in various embodiments in any suitable manner.

[0060] The present invention mainly provides an ion conducting membrane and a preparation method thereof, and a battery device using the ion conducting membrane.

[0061] The ion-conducting membrane of the present invention mainly comprises a hydrophobic polymer material and a hydrophilic polymer material. The porosity of the ion-conducting membrane is above 80% by volume, and the average pore size of the porous structure is 4 nm to 30 nm.

[0062] The present invention is mainly based on the following insights:

[0063] It has been observed that in the past, in the preparation process of porous ion conductive membranes, the pore size becomes larger as the porosity increases, and the pore size becomes smaller as the porosity decreases. Therefore, it seems impossible to solve the "paradoxical" contradictory relationship between porosity and pore size. In order to address this problem, the present invention realizes the preparation of ultra-high porosity porous membranes by constructing a graded and progressive pore channel structure, while ensuring the pore size distribution range of the nanometer-sized pore size. While maintaining the nanoscale microporous structure of the membrane, the present invention prepares a porous membrane with ultra-high porosity, thereby balancing the contradictory relationship between porosity and pore size. The porous membrane is further applied to batteries, especially flow batteries, and can show high battery efficiency, high voltage efficiency and high energy efficiency, thereby achieving a substantial improvement in battery efficiency indicators.

[0064] [First aspect]

[0065] In a first aspect of the present invention, an ion conducting membrane is provided, which is a porous membrane having a porous structure.

[0066] The ion conducting membrane of the present invention is mainly composed of polymer materials. Specifically, the material of the ion conducting membrane includes hydrophobic polymer materials and hydrophilic polymer materials.

[0067] (Hydrophobic polymer material)

[0068] In principle, there is no particular limitation on the hydrophobic polymer material, and any hydrophobic polymer material conventionally used in the art for preparing ion-conducting membranes can be used.

[0069] In some specific embodiments of the present invention, the hydrophobic polymer material can be selected from one or more of polyolefin materials or polyolefin materials having a substituent.

[0070] For the polyolefins that can be cited, it can be a homopolymer or copolymer of olefins such as ethylene, propylene, butene or unsaturated olefins containing aromatic groups. Preferably, it can be a homopolymer of ethylene or propylene or a copolymer containing the monomer. Further, for the above-mentioned polyolefins, it can further have a hydrophobic substituent, typically, it can be a halogen atom, especially a chlorine atom or a fluorine atom.

[0071] In some preferred embodiments, the hydrophobic polymer material of the present invention is selected from at least one of polyethylene, polypropylene, polyvinylidene fluoride, polytetrafluoroethylene and the like.

[0072] The hydrophobic polymer material of the present invention can mainly provide basic mechanical properties and self-supporting properties for the final ion-conducting membrane. Therefore, there is no particular limitation on the molecular weight of such hydrophobic polymer material as long as it can meet the above-mentioned functions. In some specific embodiments, such polymer can have a molecular weight of more than 800,000, preferably more than 1 million, more than 3 million, or even more than 5 million.

[0073] It should also be noted that the hydrophobic polymer material of the present invention is also allowed to have a certain content of hydrophilic groups in its molecular structure, as long as the material as a whole is a hydrophobic material in terms of its characteristics as judged by the water contact angle.

[0074] (Hydrophilic polymer material)

[0075] In principle, there is no particular limitation on the hydrophilic polymer of the present invention, and any hydrophilic polymer material conventionally used in the art for preparing ion-conducting membranes can be used.

[0076] In the hydrophilic polymer material of the present invention, the hydrophilic groups on the molecular chain are used to obtain a hydrophilic polymer that meets the requirements. The so-called meeting the requirements means that the number, density, distribution, etc. of these hydrophilic groups are sufficient to make the hydrophilic polymer material swell under the action of an aqueous solvent.

[0077] In principle, there is no particular limitation on the type of the hydrophilic group. In some preferred embodiments, these groups may be one or more of hydroxyl, amino, thiol, etc. Preferably, the hydrophilic group is hydroxyl or amino.

[0078] In a further preferred embodiment, the hydrophilic polymer material of the present invention can be selected from organic polymers containing polyhydroxy or polyamino structures, such as cellulose and its derivatives, polyalkylene alcohol ethers, copolymers excluding alcohols and olefins, olefin polymers with amide groups, and the like.

[0079] The hydrophilic polymer material of the present invention can mainly provide swelling properties during membrane processing to adjust the pore size. In addition, it can also provide cross-linking properties generated by hydrophilic groups to stabilize the size.

[0080] In some specific embodiments of the present invention, as long as the above-mentioned effects can be met, there is no particular limitation on the molecular weight, which can be adjusted according to different types of hydrophilic polymer materials.

[0081] It should also be noted that the hydrophilic polymer material of the present invention is also allowed to have a certain content of hydrophobic groups in its molecular structure, as long as the material as a whole is a hydrophilic material based on the characteristics judged by the water contact angle and has the required swelling properties.

[0082] (Other ingredients)

[0083] The ion conducting membrane of the present invention may optionally contain one or more other processing aid components in addition to the above-mentioned hydrophobic polymer material and hydrophilic polymer material.

[0084] There is no particular limitation on the type of such auxiliary components, and examples thereof include wetting agents, crosslinking agents, heat stabilizers, dispersants, lubricants, and the like.

[0085] (Composition and characteristics)

[0086] For the ion-conducting membrane of the present invention, in some preferred embodiments, the total amount of the hydrophobic polymer material and the hydrophilic polymer material is 95% by mass or more, more preferably 96% by mass or more, based on the total mass.

[0087] Furthermore, from the perspectives of mechanical properties, processability and pore size control, the ratio of the hydrophobic polymer material to the hydrophilic polymer material may generally be 1:0.8 to 3, preferably 1:0.9 to 2.8, and more preferably 1:1 to 2.6.

[0088] The structural characteristics of the pores of the ion-conducting membrane of the present invention are high porosity, which can be 80% by volume or more, preferably 82% by volume or more, and more preferably 85% by volume or more. In addition, there is no particular upper limit on the porosity in principle, and in view of processing convenience and mechanical properties, it can usually be 92% by volume or less, preferably 90% by volume or less.

[0089] Furthermore, for the pore size of the present invention, a smaller, nanometer-level average pore size can be obtained under the premise of the above-mentioned high porosity. Specifically, the average pore size of the porous structure of the present invention can be 4 to 30 nm, preferably 4.5 to 20 nm, and more preferably 5 to 10 nm.

[0090] For the ion-conducting membrane of the present invention, in view of mechanical properties and dimensional stability, it is preferred that it has a cross-linked structure inside, and the cross-linked structure can be formed with or without the aid of a cross-linking agent. In some preferred embodiments, it can be achieved by cross-linking the hydrophilic groups in the hydrophilic polymer material (under the action of a cross-linking agent).

[0091] In principle, there is no particular limitation on the thickness of the ion-conducting membrane of the present invention, and the thickness can be set according to the common thickness in the art. Preferably, the thickness of the ion-conducting membrane can be 10 to 400 μm, preferably 15 to 100 μm.

[0092] (application)

[0093] The ion-conducting membrane of the present invention can be used in various redox-type batteries. In principle, there is no particular limitation on such batteries, and examples thereof include fuel cells and liquid flow batteries.

[0094] In some preferred embodiments, the battery may be a vanadium electrolyte flow battery.

[0095] [Second aspect]

[0096] In a second aspect of the present invention, there is provided a method for preparing an ion conductive membrane for a battery, in particular, the method for preparing the ion conductive membrane in the above-mentioned [first aspect].

[0097] The method for preparing the ion-conducting membrane of the present invention is a hierarchical and progressive pore channel structure construction strategy. Specifically, the method includes: a wet film forming step, a primary pore-forming step, a secondary pore-forming step, and a phase separation step.

[0098] Among them, in the step of forming the wet film, a composition including a hydrophobic polymer material, a hydrophilic polymer material, an organic diluent and a low molecular weight component is mixed to prepare a wet film; in the step of primary pore-forming, the organic diluent in the wet film is removed to perform primary pore-forming; in the step of secondary pore-forming, the low molecular weight component in the wet film is removed to perform secondary pore-forming; in the step of phase separation, the hydrophilic polymer material and the hydrophobic polymer material are phase-separated by swelling the hydrophilic polymer material.

[0099] (Steps of wet film formation)

[0100] The wet film of the present invention refers to the original film based on the polymer composition without pore-inducing treatment.

[0101] The polymer composition used for the ion-conducting membrane of the present invention comprises, in addition to the hydrophobic polymer material, the hydrophilic polymer material and the optional processing aid described above, an organic diluent for graded pore formation and a low molecular weight component.

[0102] The organic diluent may be a non-aqueous organic solvent, which is used for subsequent extraction and pore formation, and can make the composition form a system with substantially uniform components during the process of forming a wet film.

[0103] In some preferred embodiments, the organic diluent may be a poor solvent for the organic components in the composition. Examples of organic diluents include saturated hydrocarbon-based solvents, typically white oil, liquid paraffin, and the like.

[0104] The low molecular weight components are mainly those components that can be removed by the organic solvent used in the secondary pore-forming step described below. Therefore, in addition to having a relatively low molecular weight, such components preferably also have good non-crystallization and processing fluidity. Therefore, in a further preferred embodiment of the present invention, the low molecular weight components may be polycarbonate, polyether polyamide, etc. In addition, in principle, there is no particular restriction on the molecular weight of such low molecular weight components, as long as they have sufficient solubility in the above-mentioned organic solvents, and they may generally be 5000 or less, preferably 3000 or less.

[0105] Furthermore, with regard to the content of the organic diluent and the low molecular weight component in the above-mentioned composition of the present invention, in some specific embodiments, based on the total mass of the composition, the content of the organic diluent is 50-70 mass %, preferably 55-65 mass %; the content of the low molecular weight component is 10-30 mass %, preferably 15-25 mass %.

[0106] After the above composition is mixed, a wet film can be prepared. There is no particular limitation on the method for preparing the wet film in principle, and a typical method of preparing the wet film is a blending-extrusion method. The original film obtained by extrusion can be kept at a relatively low temperature so that it has sufficient ability to maintain its shape.

[0107] (One-step pore formation)

[0108] The primary pore-forming step of the present invention is mainly to remove the organic diluent in the wet film obtained above to perform the primary pore-forming.

[0109] There is no particular limitation on the method of removing the organic diluent in principle. In some preferred embodiments, the organic diluent can be removed by extraction with an extractant. Furthermore, by using the extractant, substantially all of the organic diluent in the wet film is removed.

[0110] As the extractant, those having good solubility for the organic diluent and being poor solvents for other organic components in the wet film may be used, and in particular, those having good volatility may be used to prevent residue from occurring in the film of the present invention.

[0111] In some preferred embodiments, the extractant may be a chlorinated hydrocarbon, such as trichloroethylene, butyl chloride, carbon tetrachloride and other relatively low polar extractants, more preferably, trichloroethylene.

[0112] Furthermore, the wet membrane may be immersed in an extractant, so that the organic diluent originally in the wet membrane is fully precipitated and dissolved in the extractant.

[0113] Through the above extraction treatment, a primary pore structure can be obtained in the membrane.

[0114] Furthermore, after the above extraction treatment, the once porous membrane may be dried to remove excess extractant to obtain a dry membrane (a). The drying treatment can also stabilize the size of the dry membrane (a).

[0115] The dry film (a) obtained by a single porogenic treatment may generally have a porosity of 50 to 65 v%, preferably, the porosity may be 52 to 58 v%, for example, 54 v%, 58 v%, 60 v%, 63 v%, etc.

[0116] Furthermore, the average pore size of the pores in the dry film obtained by the primary porosification may generally be 10 nm to 50 nm, and examples thereof include 12 nm, 15 nm, 17 nm, 20 nm, 22 nm, 24 nm, 26 nm, 28 nm, 30 nm, 32 nm, 34 nm, 36 nm, 38 nm, 40 nm, 42 nm, 44 nm, 46 nm, 48 nm, etc.

[0117] (Secondary pore-forming step)

[0118] The second pore-forming step of the present invention is to remove the low molecular weight components in the wet film, that is, based on the film (dry film (a)) obtained by the first pore-forming treatment, the low molecular weight components therein are further removed.

[0119] For the removal of low molecular weight components, it can be carried out by impregnation treatment. The organic solvent used for the impregnation treatment mainly depends on the characteristics of the low molecular weight components. It is necessary that the organic solvent has good solubility (similar polarity) for the low molecular weight components and is a poor solvent for other organic components (hydrophobic polymer material and hydrophilic polymer material). This poor solvent can be caused by the high molecular weight of the hydrophobic polymer material and the hydrophilic polymer material, or it can be caused by the difference in polarity. In some specific embodiments, the organic solvent can be an amide solvent, a sulfone solvent, etc.

[0120] The above-mentioned impregnation treatment may be optionally carried out under heating conditions to promote the low molecular weight components to enter the organic solvent more fully. Preferably, the low molecular weight components are substantially completely removed by the impregnation treatment.

[0121] Through the above-mentioned impregnation treatment, a secondary pore structure can be obtained in the membrane.

[0122] Furthermore, after the above-mentioned immersion treatment, the secondary porous film can be dried to remove excess organic solvent to obtain a dry film (b). The drying treatment also has a dimensional stabilization effect on the dry film (b).

[0123] The dry film (b) obtained by the secondary porogenic treatment may generally have a porosity of 65 to 80 v%, preferably, the porosity may be 67 to 77 v%, for example, 70 v%, 72 v%, 74 v%, 76 v%, etc.

[0124] Furthermore, the average pore size of the pores in the dry film obtained by secondary porosity may generally be 7 nm to 40 nm, and examples include 10 nm, 12 nm, 15 nm, 17 nm, 20 nm, 22 nm, 24 nm, 26 nm, 28 nm, 30 nm, 32 nm, 34 nm, 36 nm, 38 nm, etc.

[0125] Due to the precipitation of low molecular weight components during the secondary porosification and the removal of organic solvents by drying, the pores obtained by the primary porosification are further reduced. Therefore, the average pore size obtained is smaller than the pores obtained after the primary porosification.

[0126] (Phase separation step)

[0127] In the phase separation step of the present invention, the hydrophilic polymer material and the hydrophobic polymer material are phase separated by swelling of the hydrophilic polymer material.

[0128] In this process, not only are new pores with small pore sizes generated through phase separation, but the volume expansion of the hydrophilic polymer material also leads to further squeezing of the pore sizes of the existing pores obtained through the two pore-forming processes. Therefore, overall, the average pore size of the pores in the membrane of the present invention is further reduced through phase separation treatment.

[0129] The phase separation step of the present invention can be carried out by using an aqueous solvent, typically by immersion in water.

[0130] The dry film (b) obtained in the secondary pore-forming step is immersed in water, optionally accompanied by heating treatment to promote sufficient swelling of the hydrophilic polymer material.

[0131] Through the above-mentioned swelling treatment, the average pore size of the pores in the membrane can be further controlled.

[0132] Furthermore, after the swelling treatment, the film may be dried to remove water to obtain a dry film (c). The drying treatment also has a dimensional stabilization effect on the dry film (c).

[0133] The dry film (c) obtained above may generally have a porosity of more than 80 v%, preferably, the porosity may be 82-92 v%, for example, 84 v%, 86 v%, 88 v%, 90 v%, etc.

[0134] Furthermore, the average pore size of the pores in the finally obtained dry film (c) may generally be 4 nm to 30 nm, preferably 4.5 nm to 20 nm, and more preferably 5 nm to 10 nm, including 5 nm, 8 nm, 10 nm, 12 nm, 15 nm, 17 nm, 20 nm, 22 nm, 24 nm, 26 nm, 28 nm, etc.

[0135] The dry film (c) can be used as the ion conducting membrane of the present invention, or the dry film can be further subjected to heat setting, heat relaxation and other treatments to obtain the final ion conducting membrane.

[0136] (Other steps)

[0137] In some preferred embodiments of the present invention, from the perspective of improving the final dimensional stability, mechanical properties, and pore size controllability of the final ion conductive membrane, the membrane may also be cross-linked during the preparation of the ion conductive membrane of the present invention.

[0138] The cross-linking treatment of the present invention may be performed via a cross-linking reaction of the hydrophilic groups in the hydrophilic polymer material with or without the use of an additional cross-linking agent.

[0139] In some specific embodiments of the present invention, the cross-linking step can be performed simultaneously with or after the phase separation step. From the perspective of pore size controllability, it is preferably performed simultaneously with the phase separation step.

[0140] In some preferred embodiments, while the dry film (b) is impregnated with an aqueous solvent, a crosslinking agent can be added to the solvent (the temperature can be adjusted if necessary) so that a crosslinked structure is generated in the film while swelling. There is no particular restriction on the type and amount of the crosslinking agent, which can be selected according to the type and content of the hydrophilic polymer material. Performing crosslinking while swelling can make it easier to control the degree of swelling and the size of the pores.

[0141] [Third aspect]

[0142] The third aspect of the present invention mainly provides a battery device using or including the ion conductive membrane described above. In principle, there is no particular limitation on such a battery device, as long as it can be listed as a fuel cell, a liquid flow battery, etc.

[0143] In some preferred embodiments of the present invention, the battery device is a liquid flow battery device, in particular an iron-chromium liquid flow battery or an all-vanadium liquid flow battery.

[0144] Example

[0145] The embodiments of the present invention will be described in detail below in conjunction with the examples, but those skilled in the art will appreciate that the following examples are only used to illustrate the present invention and should not be considered to limit the scope of the present invention. If no specific conditions are specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be obtained commercially.

[0146] Test Method :

[0147] (1) Porosity test method

[0148] The porosity was tested using the liquid infiltration method.

[0149] For example, the porosity of a membrane is calculated as the ratio of the volume of the membrane pores occupied by the wetting liquid to the total volume of the membrane.

[0150] ① Prepare an aqueous solution containing 10% n-butanol as the infiltration liquid, and the test density is g1.

[0151] ② Take the film sample in the embodiment and dry it at above 110°C, and then record the mass as M1.

[0152] ③ Completely immerse the dried sample in the infiltration liquid and place it in a vacuum oven at 25°C and -0.09MPa for negative pressure infiltration for 24 hours.

[0153] ④ After taking out the soaked sample, wipe off the water stains on the surface, and record the mass as M2. Calculate the mass change ω=M2-M1, and measure the length, width and thickness of the regular sample to calculate the membrane volume and record it as v1. Then the membrane porosity β=(ω / g1) / v1

[0154] (2) Test method for average pore size

[0155] The average pore size was tested using the liquid-liquid displacement method.

[0156] For example, after the membrane sample is infiltrated with the infiltration liquid that completely infiltrates it, a liquid that is immiscible with the infiltration liquid is used as a displacement liquid to displace the infiltration liquid out of the through-hole channel. The pore size data can be obtained through the liquid flow rate and pressure data according to the Washburn formula, and the average pore size data can be output through statistical calculation.

[0157] D = 4γCosθ / p

[0158] In the formula: D = pore diameter; γ = surface tension of liquid; θ = contact angle; p = pressure difference

[0159] ① The sample membrane is vacuum infiltrated in the infiltration liquid, then sealed and clamped with a clamp and placed in the displacement liquid. High-purity nitrogen is used to gradually apply pressure on one side, and the liquid flow and applied pressure changes on the other side are continuously collected and recorded during the process.

[0160] ② According to the changes in pressure and flow rate under different pressures, test records of pore points of different sizes are carried out, and then the average pore size of the output membrane is calculated.

[0161] Example 1

[0162] 100 g of ultra-high molecular weight polyethylene (molecular weight 5 million), 100 g of ethylene-vinyl alcohol copolymer (molecular weight 350,000), 50 g of polyetherimide (molecular weight 2000), 50 g of sodium polystyrene sulfonate, and 5 g of calcium stearate were respectively added to 500 g of white oil, and the mixture was dispersed and mixed at high speed at 30°C for 2 hours to obtain a homogeneous blended paste.

[0163] The above homogenized blended paste was added into a twin-screw extruder, heated to 220°C for melt mixing and extrusion, and after further homogenization, calendering and quenching at 10°C to obtain an oil-containing wet film.

[0164] The above oil-containing wet membrane was extracted in trichloroethylene to extract white oil, and then dried at 90°C to obtain a porous dry membrane. At this time, the membrane porosity was 57% and the average pore size was 10 nm.

[0165] The primary porous dry membrane was immersed in DMF solution at 50°C for 10 min, and the polyetherimide was dissolved. It was then heated to 140°C to obtain a secondary porous dry membrane. At this time, the membrane porosity was 78% and the average pore size was 7 nm.

[0166] The secondary porous dry membrane was immersed in an aqueous solution of sodium salt of 1,4-dipentyl sulfosuccinate, which contained 10% boric acid as a cross-linking agent. It was infiltrated and swelled at 40°C for 5 minutes to produce hydrophilic phase separation and cross-linking reaction. The membrane was then clamped and fixed, and dried at 100°C to obtain a tertiary porous dry membrane. At this time, the membrane porosity was 82% and the average pore size was 5 nm.

[0167] Example 2

[0168] 100 g of ultra-high molecular weight polyethylene (molecular weight 5 million), 200 g of ethylene-vinyl alcohol copolymer (molecular weight 350,000), 50 g of polyetherimide (molecular weight 8000), 50 g of sodium polystyrene sulfonate, and 5 g of calcium stearate were respectively added to 600 g of white oil, and the mixture was dispersed and mixed at high speed at 30°C for 2 hours to obtain a homogeneous blended paste.

[0169] The above homogenized blended paste was added into a twin-screw extruder, heated to 220°C for melt mixing and extrusion, and after further homogenization, calendering and quenching at 10°C to obtain an oil-containing wet film.

[0170] The above oil-containing wet membrane was extracted in trichloroethylene and dried at 90°C to obtain a porous dry membrane. At this time, the membrane porosity was 62% and the average pore size was 13 nm.

[0171] The primary porous dry membrane was immersed in DMF solution at 50°C for 10 min, and the polyetherimide was dissolved. It was then heated to 140°C to obtain a secondary porous dry membrane. At this time, the membrane porosity was 80% and the average pore size was 10 nm.

[0172] The secondary porous dry membrane was immersed in an aqueous solution of sodium salt of 1,4-dipentyl sulfosuccinate, which contained 20% boric acid as a cross-linking agent. It was infiltrated and swelled at 40°C for 5 minutes to produce hydrophilic phase separation and cross-linking reaction. The membrane was then clamped and fixed, and dried at 100°C to obtain a tertiary porous dry membrane. At this time, the membrane porosity was 88% and the average pore size was 7 nm.

[0173] Example 3

[0174] 100 g of ultra-high molecular weight polyethylene (molecular weight 6.5 million), 100 g of polyacrylamide (8 million), 50 g of polyetherimide (molecular weight 2000), 50 g of sodium lignin sulfonate, and 5 g of calcium stearate were respectively added to 500 g of white oil, and mixed at high speed at 30°C for 2 hours to obtain a homogeneous blended paste.

[0175] The above homogenized blended paste was added into a twin-screw extruder, heated to 170°C for melt mixing and extrusion, and after further homogenization, calendering and quenching at 10°C to obtain an oil-containing wet film.

[0176] The above oil-containing wet membrane was extracted in trichloroethylene and dried at 90°C to obtain a porous dry membrane. At this time, the membrane porosity was 61% and the average pore size was 13 nm.

[0177] The primary porous dry membrane was immersed in DMF solution at 70°C for 10 min, and then heated to 140°C for drying to obtain a secondary porous dry membrane. At this time, the membrane porosity was 76% and the average pore size was 8 nm.

[0178] The secondary porous dry membrane was immersed in an aqueous solution of sodium salt of 1,4-dipentyl sulfosuccinate, which also contained 10% sodium persulfate. It was infiltrated and swelled at 40°C for 5 minutes to produce hydrophilic phase separation and cross-linking reaction. The membrane was then clamped and fixed, and dried at 100°C to obtain a tertiary porous dry membrane. At this time, the membrane porosity was 85% and the average pore size was 5 nm.

[0179] Example 4

[0180] 100 g of polytetrafluoroethylene (molecular weight 1 million), 100 g of polyacrylamide (molecular weight 7 million), 100 g of polyetherimide (molecular weight 2000), 50 g of sodium lignin sulfonate, and 5 g of calcium stearate were respectively added to 650 g of white oil, and mixed at high speed at 30° C. for 2 hours to obtain a homogeneous blended paste.

[0181] The above homogenized blended paste was added into a twin-screw extruder, heated to 170°C for melt mixing and extrusion, and after further homogenization, calendering and quenching at 10°C to obtain an oil-containing wet film.

[0182] The above oil-containing wet membrane was extracted in trichloroethylene and dried at 90°C to obtain a porous dry membrane. At this time, the membrane porosity was 63% and the average pore size was 15 nm.

[0183] The primary porous dry membrane was placed in DMF, immersed at 70°C for 10 min, and then heated to 150°C to obtain a secondary porous dry membrane. At this time, the membrane porosity was 75% and the average pore size was 7 nm.

[0184] The secondary porous dry membrane was immersed in an aqueous solution of sodium salt of 1,4-dipentyl sulfosuccinate, which also contained 10% sodium persulfate. It was infiltrated and swelled at 40°C for 5 minutes to produce hydrophilic phase separation and cross-linking reaction. The membrane was then clamped and fixed, and dried at 100°C to obtain a tertiary porous dry membrane. At this time, the membrane porosity was 89% and the average pore size was 5 nm.

[0185] Example 5

[0186] 100 g of polytetrafluoroethylene (molecular weight 1 million), 100 g of polyacrylamide (molecular weight 7 million), 100 g of polyetherimide (molecular weight 2000), 50 g of sodium lignin sulfonate, and 5 g of calcium stearate were respectively added to 650 g of white oil, and mixed at high speed at 30° C. for 2 hours to obtain a homogeneous blended paste.

[0187] The above homogenized blended paste was added into a twin-screw extruder, heated to 170°C for melt mixing and extrusion, and after further homogenization, calendering and quenching at 10°C to obtain an oil-containing wet film.

[0188] The above oil-containing wet membrane was extracted in trichloroethylene and dried at 90°C to obtain a porous dry membrane. At this time, the membrane porosity was 63% and the average pore size was 15 nm.

[0189] The primary porous dry membrane was placed in DMF, immersed at 70°C for 10 min, and then heated to 150°C to obtain a secondary porous dry membrane. At this time, the membrane porosity was 75% and the average pore size was 7 nm.

[0190] The secondary porous dry membrane was immersed in an aqueous solution of sodium salt of 1,4-dipentyl sulfosuccinate, and was infiltrated and swelled at 40°C for 5 minutes to produce a hydrophilic phase separation. The membrane was then clamped and fixed, and dried at 140°C for a heated self-crosslinking reaction to obtain a tertiary porous dry membrane. At this time, the membrane porosity was 90% and the average pore size was 5 nm.

[0191] Comparative Example 1:

[0192] The same as Example 1, except that no swelling and cross-linking treatment was performed, and a secondary porous dry membrane with a membrane porosity of 78% and an average pore size of 7 nm was used as the ion conductive membrane.

[0193] Comparative Example 2:

[0194] The same as Example 1, except that polyetherimide is not used and the dissolution treatment of polyetherimide with DMF is not performed, a dry film is obtained after the white oil is extracted, and swelling and cross-linking treatment are directly performed to obtain a membrane with a porosity of 74% and an average pore size of 6 nm.

[0195] Comparative Example 3:

[0196] DuPont Nafion NR212 membrane was used as the ion conducting membrane.

[0197] The ion-conducting membrane samples prepared in the above examples were installed in a single-cell system of an all-vanadium redox flow battery for performance testing. 2 The charge and discharge efficiency test was carried out at a current density of , and the current efficiency, voltage efficiency, and energy efficiency data obtained are as shown in Table 1 and Table 2:

[0198]

[0199] The ultra-high porosity porous membrane prepared by the technical solution of the present invention and the all-vanadium liquid flow battery assembled therefrom show high current efficiency, high voltage efficiency and high energy efficiency.

[0200] It should be noted that, although the technical solution of the present invention is introduced with specific examples, those skilled in the art will appreciate that the present invention should not be limited thereto.

[0201] The embodiments of the present invention have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and variations will be apparent to those of ordinary skill in the art without departing from the scope and spirit of the described embodiments. The selection of terms used herein is intended to best explain the principles of the embodiments, practical applications, or technical improvements in the market, or to enable other persons of ordinary skill in the art to understand the embodiments disclosed herein.

Claims

1. An ion conducting membrane, characterized in that The ion-conducting membrane has a porous structure, and includes a hydrophobic polymer material and a hydrophilic polymer material, wherein the hydrophilic polymer material has water-swellability. in, The porosity of the ion-conducting membrane is greater than 80% by volume, and the average pore size of the porous structure is 4 nm to 30 nm.

2. The ion conducting membrane according to claim 1, characterized in that The mass ratio of the hydrophobic polymer material to the hydrophilic polymer material in the ion conducting membrane is 1:0.8-3.

3. The ion conducting membrane according to claim 1 or 2, characterized in that: The hydrophilic polymer material has one or more hydrophilic groups in its molecular structure.

4. The ion conducting membrane according to claim 1 or 2, characterized in that: In the ion-conducting membrane, the total content of the hydrophobic polymer material and the hydrophilic polymer material is greater than 95% by mass, based on the total mass of the membrane. Optionally, the ion-conducting membrane further comprises one or more processing aids.

5. The ion conducting membrane according to claim 1 or 2, characterized in that: The ion-conducting membrane is also cross-linked.

6. The method for preparing an ion conducting membrane according to claim 1 or 2, characterized in that: It includes: The steps of wet film formation, primary pore formation, secondary pore formation and phase separation are as follows: in: In the step of forming the wet film, a composition including a hydrophobic polymer material, a hydrophilic polymer material, an organic diluent and a low molecular weight component is mixed to prepare a wet film; In the step of primary pore formation, the organic diluent in the wet film is removed to perform primary pore formation; In the step of secondary pore formation, the low molecular weight components are removed to perform secondary pore formation; In the phase separation step, the hydrophilic polymer material and the hydrophobic polymer material are phase separated by swelling of the hydrophilic polymer material.

7. The method according to claim 6, characterized in that In the step of forming the wet film, the composition is substantially a system with uniform components; based on the total mass of the composition, the content of the organic diluent is 50% to 70% by mass, and the content of the low molecular weight component is 10% to 30% by mass.

8. The method according to claim 6 or 7, characterized in that: In the primary pore-forming step, the organic diluent is removed by using an extractant, and the extractant is a poor solvent for the hydrophobic polymer material, the hydrophilic polymer material and the low molecular weight component.

9. The method according to claim 6 or 7, characterized in that: In the secondary pore-forming step, the low molecular weight components are removed by an organic solvent, and the organic solvent is a poor solvent for the hydrophobic polymer material and the hydrophilic polymer material.

10. The method according to claim 6 or 7, characterized in that: In the phase separation step, the hydrophilic polymer material is swollen by an aqueous solvent.

11. The method according to claim 6 or 7, characterized in that: The method further comprises a cross-linking step, in which a cross-linked structure is formed at least by the hydrophilic polymer material.

12. The method according to claim 11, characterized in that The cross-linking step is performed simultaneously with the secondary pore formation.

13. The method according to claim 6 or 7, characterized in that: After the primary pore-forming step, a dry film (a) is obtained, wherein the porosity of the dry film (a) is 50% to 65% by volume and the average pore diameter is 10 to 50 nm.

14. The method according to claim 6 or 7, characterized in that: After the secondary pore-forming step, a dry film (b) is obtained, wherein the porosity of the dry film (b) is 65 volume % to 80 volume % and the average pore diameter is 7 to 40 nm.

15. The method according to claim 6 or 7, characterized in that: After the phase separation step, a dry film (c) is obtained, wherein the porosity of the dry film (c) is 80% to 92% by volume and the average pore diameter is 4 to 30 nm.

16. A redox battery, characterized in that: The battery comprises or uses the ion conducting membrane according to any one of claims 1 to 5, or comprises or uses the ion conducting membrane obtained by the method according to any one of claims 6 to 15.

17. The battery according to claim 16, characterized in that The battery includes any one of a flow battery and a fuel cell.

Citation Information

Patent Citations

  • Blending membrane for all-vanadium redox flow battery and preparation method for blending membrane

    CN102881853A

  • All-vanadium redox flow battery membrane and preparation method thereof

    CN107658478A

  • A zwitterionic membrane for all vanadium liquid flow batteries

    CN109103483A

  • Multi-layer composite film for flow battery and preparation method thereof

    CN112151825A

  • Application of polymer porous separation membrane in liquid flow energy storage battery

    CN103682387A